A Study of Chinese College Students’ English Writing Strategies - Hui, Chen; Xinguang, SHAO (Advances in Social Sciences Research Journal, 2015)
The study investigates how Chinese college students use strategies in English writing with the help of questionnaires. The results show that many students don’t do well in using metacognitive strategies and social strategies when they do English writing exercises. Most students need to develop the good habit of using strategies in English writing, trying hard to improve their writing ability. English teachers should make efforts to help their students get the knowledge of strategies, paying much attention to the training of writing strategies in the classroom teaching. Key words: Chinese college students, English writing strategies, questionnaires, training